Influence of climate conditions projected for World Cup 2022 in Qatar on soccer players` performance of repeated maximal exercises - Chmura, P.; Konefal, M.; Rokita, A.; Blazejczyk, K.; Andrzejewski, M.; Chmura, J. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: Top-level soccer tournaments such as the World Cup are held in variable, often adverse, weather conditions. The ambient conditions are important modifiers of players` physiological responses to exercise (Nassis et al.. 2015). The study aims to seek relationships between players` ability to perform repeated maximal exercise and climate conditions for the 2022 FIFA World Cup in Qatar simulated in an environmental test chamber. Methods: The study group will consist of 24 male soccer players aged 17-18 years. The players will perform an exercise test comprising ten 6-second maximal exercises on a cycloergometer (MONARK LT2). with 90-second passive rest breaks between. The measured variables will include lactate, acid-base homeostasis, and arte rial-blood gas levels and heart rate. The measurements will be taken twice in an environmental test chamber (Weiss Technik WK-26): 1) in thermo-neutral conditions (20.5°C, 58.7% RH); and 2) in conditions typical for 21st November in Doha. Qatar (day and place of the 2022 World Cup inauguration) (28.5 ± 1.92°C. 58.7 ± 8.64% RH). The study will be conducted in June 2018, funded from the National Science Center grant no. 379162. Expected results: Significant differences in players` physiological and biochemical parameters in thermo-neutral and in climate conditions of Qatar are expected (Chmura et al.. 2017). According to Grantham et al.. (2010) playing soccer in an ambient temperature of 22°C does not incur a risk of body overheating. This risk is low in the temperature range of 22 - 28°C. and high at above 28°C. Players` incremental fatigue in high ambient temperatures reduces the distance covered by them with a high intensity in the last phase of the game. More over fatigue also decreasesthe number of performed explosive efforts, e.g. accelerations, sprints, and jumps (Mohr et al.. 2010). Conclusion: Data on players` responses to exercise in heat stress should be used by coaches in their player preparation programs for the 2022 FIFA World Cup in Qatar.